Técnica “ITEL” para mejorar la lectoescritura de los educandos del primer grado de la I.E. 80706 Moche - Quipuzco Zamora, Monica Patricia (2019)
ABSTRACT The purpose of this research is to determine the “Technique “ITEL” to improve literacy of first grade students of I.E. 80706 Moche”, which is one of the problems, whereby the students present difficulties in their present and future learning. The sample population was made up of 60 students, the experimental group being the students of section "B" and the control group the students of section "A". The type of research is quasi-experimental with pre and posttest of the experimental and control group. The application of the “ITEL” Technique according to the results of the posttest, shows us that the students who are the subject of our research, have been able to significantly improve literacy learning.